Sustainable manufacturing for turning of Inconel 718 using uncoated carbide inserts. (2022) - Kumar Bohidar, Shailendra; Surakasi, Raviteja; Karuna, M.S.; Janardhana, Kedri; Louies Praveen, S.; Narayan, Puneet
Abstract: In this work, sustainability in manufacturing is accomplished by introduction of a vortex tube. Vortex tube is a mechanical device that separates the hot compressed air and the cold air that flows through the tube and exits the cold air alone on to the work piece. The objective of the work is to implement sustainability in the manufacturing process for turning of Inconel 718 using coated carbide inserts. This is achieved by the implementation of vortex tube, which is used for cooling the cutting tools in turning and milling operations. Modern CNC machine tools are embedded with the vortex tube for effective heat removal process from the cutting tool. By the implementation of vortex tube, the liquid coolant is totally eliminated. The work piece considered in this work is Inconel 718. 38 mm diameter and 75 mm long cylindrical bar stock is used in this work as the test specimen for turning using uncoated carbide inserts. Design of experiments are used to conduct 27 set of experiments and for each set of experiments, the flank are measured and recorded. The flank wear is found to be decreased upto 7.2% with the implementation of the vortex tube in the turning process. The main effects plot for means for the flank wear with and without vortex tube is plotted and discussed.